PENGARUH INTERAKSI HARA NITROGEN DAN FOSFOR TERHADAP PERTUMBUHAN TANAMAN JAGUNG (Zea Mays L) PADA TANAH REGOSOL DAN LATOSOL - Arifin Fahmi; Sri Nuryani H Utami; Bostang Radjagukguk (Research Center for Biology-Indonesian Institute of Sciences, 2010)
Nitrogen (N) and Phosphorus (P) are essential nutrients for plant.The deficiency one of these nutrients will be limiting the plant growth.A glass house experiment with one treatment factor was conducted to study the effect and interaction of N and P fertilizers application on maize growth in regosol and latosol soils. The results show that the interaction of N and P fertilizers application(N 1 P 1) on regosol had a significant influence to plant height on 3 to 7 weeks after planting, whilst on latosol had a significant influence to plant height on 1 to 5 weeks after planting. The shoot dry weight, root dry weight and total dry weight of maize on regosols and latosol soils were significantly influenced by the interaction of N and P fertilizers application (N 1 P 1). There were a positive correlation between N and P fertilizers application on both soils types to the total plant dry weight.